Taking the stress out of homework : organizational, content-specific, and test prep strategies to help your children help themselves - Freireich, Abby; Platzer, Brian (Avery, an imprint of Penguin Random House, 2020)
"Taking the Stress out of Homework breaks down for parents exactly when and how to offer homework support. Whether your child's stress point is executive functioning--the ability to plan or organize--or a subject-specific struggle in math, reading, writing, or standardized test-preparation, Abby and Brian use real-life stories to provide individualized, actionable advice." -- Amazon.com.